PENELUSURAN AKAR HADITS - Damanhuri, Damanhuri (Jurnal Ilmiah Peuradeun, 2014)
Hadits has been born since fourteen centuries ago, the same age as the birth of Islam conveyed by the Prophet Muhammad SAW. Over time, the hadits is now available in a variety of books, in fiqh, tafsir, sirah, morals, article on Islamic studies, even various electronic media. Therefore it could be prophetic narrations it will experience a shift in the text or oversight in the quote. Consequently misuse or forgery wide open function. Posts wants to reveal how someone who was about to conduct a search of a hadits that the origin can be ascertained the validity of the hadits, is it true of the words of the Prophet Muhammad SAW or not, whether he is qualified valid or weak, whether he is there in the book of hadits collection or not. Necessary to determine their authenticity and tracking system that measure can be taken by the reviewer. This article aims to give a simple direction in order to ward off some of the assumptions that lead to the negative charges of the hadits, that hadits it is completely free of accusations-accusations that lead to disputes and misunderstandings.